USE OF MATHEMATICAL APPARATUS OF THE PETRI-MARKOV’S NETWORKS FOR DEFINITION OF TEMPORARY AND PROBABILISTIC CHARACTERISTICS OF THE CONTROL SYSTEM BY THE HIGH-LOADED WEB PORTALS WITH THE INCREASED FAULT TOLERANCE - R. N. Akinshin; A. N. Ivutin; D. O. Yesikov; I. A. Strahov (Научный вестник МГТУ ГА)
The Petri-Markov’s model of parallel process is considered. By means of model of "competitions" mechanisms of interaction of competing inquiries in the distributed system are considered. The control system of the high-loaded web portals with the increased fault tolerance is developed. The method of imitating modeling is considered, experimental definition of temporary characteristics of the developed web portal and load testing of system is carried out.